PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE, FREE CASH FLOW, DAN DIVIDEND PAYOUT RATIO TERHADAP MANAJEMEN LABA MELALUI MANIPULASI AKTIVITAS RILL (Studi Pada Perusahaan Yang terdaftar pada jakarta islamic index periode 2010 – 2013) - Djauhar Edi; Yohani Yohani; Tri Hidayanti (Neraca, 2015)
This research aims to examine the effect of good corporate governance mechanism which include : the size of audit committee,the proportion of independent of commissioner ,the size of directors ,institutional ownership ,as well as the effect of leverage ,free cash flow ,and dividend payout ratio to earnings management through the manipulation of real activity.Earnings management in this research is measured using abnormal cash flow operations ,abnormal discretionary expenses ,and abnormal productions.This research used samples from 80 companies listed on jakarta Islamic Index,by using purposive sampling which were published financial report among 2010-2013.The method of analysis of this research used multiple linear regression. The result of this research show that partially leverage and free cash flow Significantly influence earning management through a proxy abnormal cash flow Operations and abnormal productions. Partially institutional ownership and free cash flow significantly influence earning management through a proxy abnormal discretionary expenses,while other independent variables no significant influence on earning management through the manipulation of real activity.Simultaneous research result show that good corporate governance mechamise,leverage ,free cash flow,and dividend payout ratio significantly influence earning management through the manipulation of real activity.